Teaching implementation science in a new Master of Science Program in Germany: a survey of stakeholder expectations. - Ullrich, Charlotte; Mahler, Cornelia; Forstner, Johanna; Szecsenyi, Joachim; Wensing, Michel (Implementation Science, 2017)
Background: Implementation science in healthcare is an evolving discipline in German-speaking countries. In 2015, the Medical Faculty of the University of Heidelberg, Germany, implemented a two-year full-time Master of Science program Health Services Research and Implementation Science. The curriculum introduces implementation science in the context of a broader program that also covers health services research, healthcare systems, research methods, and generic academic skills. Our aim was to assess the expectations of different stakeholder groups regarding the master's program.Methods: An online survey listing desired competencies of prospective graduates was developed and administered to four groups: national experts in the field (including potential employers of graduates), teaching staff, enrolled students, and prospective students (N = 169). Competencies were extracted from the curriculum's module handbook. A five-point Likert scale was used for the assessment of 42 specific items. Data were analyzed descriptively.Results: A total of 83 people participated in the survey (response rate 49%). The online survey showed a strong agreement across the groups concerning the desired competencies of graduates. About two-thirds of the listed competencies (27 items) were felt to be crucial or very important by 80% or more of participants, with little difference between stakeholder groups. Of the eight items specifically related to implementation in practice, six were in this category. Knowledge of implementation strategies (90% very important), knowledge of barriers and enablers of implementation (89%), and knowledge of evidence-based practice (89%) were the top priorities.Conclusions: The master's program is largely orientated towards the desired competencies of graduates according to students, teaching staff, and national experts.